2016
DOI: 10.1016/j.dib.2015.11.060
|View full text |Cite
|
Sign up to set email alerts
|

Feedback-related potentials in a gambling task with randomised reward

Abstract: Event-related potentials (ERPs) time-locked to decision outcomes are reported. Participants engaged in a gambling task (see [1] for details) in which they decided between a risky and a safe option (presented as different coloured shapes) on each trial (416 in total). Each decision was associated with (fully randomised) feedback about the reward outcome (Win/Loss) and its magnitude (varying as a function of decision response; 5–9 points for Risky decisions and 1–4 points for Safe decisions). Here, we show data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Two studies did not find amplitude differences between gain and loss outcomes (Santesso et al, 2011 ; Telpaz and Yechiam, 2014 ), and three studies reported the opposite findings (Schuermann et al, 2012 ; Zheng et al, 2015 ; Endrass et al, 2016 ). Five studies did not report any valence effects (Oberg et al, 2011 ; Sun et al, 2015 ; Mushtaq et al, 2016 ; Wang et al, 2017 ; Watts et al, 2017 ). Nine out of the 11 studies reporting magnitude effects found consistent results with a larger P3 amplitude for larger magnitude outcomes than for smaller magnitude outcomes, irrespective of whether it was a gain or loss (Wu and Zhou, 2009 ; Polezzi et al, 2010 ; Rigoni et al, 2010 ; Santesso et al, 2011 ; Ibanez et al, 2012 ; Yang et al, 2013 , 2015 ; Zhao et al, 2016 ; Wang et al, 2017 ), whilst the two other studies found the opposite effect, with larger P3 amplitude for smaller magnitude outcomes compared to larger magnitude outcomes (Zhang et al, 2013 ; Mushtaq et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies did not find amplitude differences between gain and loss outcomes (Santesso et al, 2011 ; Telpaz and Yechiam, 2014 ), and three studies reported the opposite findings (Schuermann et al, 2012 ; Zheng et al, 2015 ; Endrass et al, 2016 ). Five studies did not report any valence effects (Oberg et al, 2011 ; Sun et al, 2015 ; Mushtaq et al, 2016 ; Wang et al, 2017 ; Watts et al, 2017 ). Nine out of the 11 studies reporting magnitude effects found consistent results with a larger P3 amplitude for larger magnitude outcomes than for smaller magnitude outcomes, irrespective of whether it was a gain or loss (Wu and Zhou, 2009 ; Polezzi et al, 2010 ; Rigoni et al, 2010 ; Santesso et al, 2011 ; Ibanez et al, 2012 ; Yang et al, 2013 , 2015 ; Zhao et al, 2016 ; Wang et al, 2017 ), whilst the two other studies found the opposite effect, with larger P3 amplitude for smaller magnitude outcomes compared to larger magnitude outcomes (Zhang et al, 2013 ; Mushtaq et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…Out of the 43 studies measuring early error-detection components, 34 studies reported larger amplitudes for loss than for gain feedback (Gehring and Willoughby, 2002 ; Nieuwenhuis et al, 2004 ; Yu and Zhou, 2006 , 2009 ; Goyer et al, 2008 ; Li et al, 2009 ; Wu and Zhou, 2009 ; Gu et al, 2010 ; Leng and Zhou, 2010 , 2014 ; Marco-Pallares et al, 2010 ; Polezzi et al, 2010 ; Rigoni et al, 2010 ; Nelson et al, 2011 ; Santesso et al, 2011 ; Heitland et al, 2012 ; Ibanez et al, 2012 ; Schuermann et al, 2012 ; Zottoli and Grose-Fifer, 2012 ; Leicht et al, 2013 ; Luo and Qu, 2013 ; Zhang et al, 2013 , 2014 ; Zhu et al, 2014 , 2016a , b ; Mushtaq et al, 2015 , 2016 ; Sun et al, 2015 ; Endrass et al, 2016 ; Kardos et al, 2016 ; Kokmotou et al, 2017 ; Wang et al, 2017 ; Watts et al, 2017 ). Ma et al ( 2011 ) reported the opposite effect, showing larger early error-detection component amplitudes in response to gain feedback compared to loss feedback.…”
Section: Resultsmentioning
confidence: 99%